Review of reconfigurable /UWB antenna for interweave cognitive radio applications. Issue 2 (3rd April 2019) - Abdulhameed, Abdulghafor Abdulghafar; Alhamdawee, Ehsan Mohsen; Hayder, Israa Mahmood
ABSTRACT: This paper presents a brief evaluation and discussion of five reconfigurable/ultra-wideband (UWB) antenna configurations that are used for cognitive radio (CR) applications. The ultra-wideband antenna is used as a sensing service while the reconfigurable antenna is used for communications. Comparison among different switching techniques is also discussed. All parameters affecting the design of the sensing and communication antennas are briefly discussed, with a summary of the most common switching diodes and their biasing networks.